Peningkatan Kemampuan Berhitung Permulaan Melalui Media Bahan Alam - Ida Ayu Marcha Jayanthi; Marsono Marsono; Gautama Jayadiningrat Made; Suardika I Komang (Generasi Emas: Jurnal Pendidikan Islam Anak Usia Dini, 2022)
Finding out whether natural material media can be effort to improve numeracy ability of children aged 5-6 years in PAUD Kumara Ngurah Rai II, is the purpose of this study, considering the problems experienced in PAUD Kumara Ngurah Rai II, namely the limited provision of concrete media in early numeracy which requires large enough budget. Class action research or commonly called PTK is type of this study, the object observed is the early numeracy abilities and 22 children aged 5-6 years in PAUD Kumara Ngurah Rai II Getasan Village, Petang District, Badung Regency consisting of 7 women and 15 men will be subject of this study. PTK was held early March 2022, then resumed in April to May 2022 the total is 3 months. Data collection methods used are teacher observation sheets, interviews and documentation. Divided into 2 cycles, research in cycle I children have increased compared to the results of pre-action, namely the percentage of developing according to expectations as many as 8 people (36.4%) to 9 people (40.90%) but the success criteria have not been achieved so that it continues to cycle II with an increase to develop very well as many as 19 people at a percentage of 86.36%. Results of the study showed that natural material media can be used to improve the early numeracy ability of children aged 5-6 years at PAUD Kumara Ngurah Rai II Getasan Village, Petang District, Badung Regency.